Pengaruh CEO Narsisme, CEO Duality dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2022-2023 - Anik Widiani; Fitri Ella Fauziah Fauziah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to determine the effect of CEO Narcissism, CEO Duality, and Company Size on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange for the 2022-2023 period. The sample selection used a purposive sampling technique with the following criteria: 1). Manufacturing companies listed on the Indonesia Stock Exchange for the 2022-2023 period; 2). Manufacturing companies that consistently publish annual financial reports for the 2022-2023 period; 3). Financial reports presented in Rupiah currency; 4). Companies that provide complete data to measure the variables in the study, based on these criteria, 209 samples were obtained. Secondary data were obtained from financial reports via the website www.idx.co.id and the company's official website. The study used a quantitative descriptive method with hypothesis testing through multiple linear regression using IBM SPSS version 25. The results indicated that CEO Narcissism and CEO Duality had no significant effect on financial performance, with significance values of 0.191 and 0.558 (>0.05), respectively. Neither narcissistic traits nor dual leadership in CEOs increase the effectiveness of the company's asset utilization in generating profits and have the potential to create agency problems due to weak oversight. Conversely, company size has a positive and significant effect on financial performance (sig. 0.004 < 0.05). This indicates that companies with large assets have a better ability to optimize resources, expand operations, and increase profitability.